Stereotactic partial breast irradiation in primary breast cancer: A comprehensive review of the current status and future directions - Takanen, Silvia; Pinnarò, Paola; Farina, Ilaria; Sperati, Francesca; Botti, Claudio; Vici, Patrizia; Soriani, Antonella; Marucci, Laura; Sanguineti, Giuseppe (Frontiers in Oncology, 2022)
In selected low-risk breast cancer patients, accelerated partial breast irradiation (APBI) may represent an alternative option to the whole breast irradiation to reduce the volume of irradiated breast and total treatment duration. In the last few years, preliminary data from clinical trials showed that stereotactic partial breast radiotherapy may have the advantage to be less invasive compared to other APBI techniques, with preliminary good results in terms of local toxicity and cosmesis: the use of magnetic resonance, fiducial markers in the tumor bed, and new breast devices support both a precise definition of the target and radiation planning. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021257856, identifier CRD42021257856.